Effects of La and Ce doping on electronic structure and optical properties of janus MoSSe monolayer. (March 2021) - Do, Thi-Nga; Nguyen, C.V.; Tan, Lam V.; Idrees, M.; Amin, Bin; Hieu, Nguyen V.; Hoai, Nguyen T.X.; Hoa, Le T.; Hieu, Nguyen N.; Phuc, Huynh V.
Abstract: In this work, the doping effects of rare-earth La and Ce atoms on electronic and optical properties of Janus MoSSe monolayer are investigated by means of first principles calculations. Our results imply that when one La and Ce doped to one S or Se side of Janus MoSSe monoalayer, it leads to a decrease in the band gap and results in the transition from direct to indirect. With increasing the La and Ce doping concentration, the Janus MoSSe monolayer switched from semiconductor to metal. Moreover, we find that effective masses of all the La and Ce doped Janus MoSSe systems are decreased as compared to pristine state, rendering their high carrier mobility. Furthermore, all the La and Ce doped MoSSe systems have red shift and possess high absorption ability in the visible and infrared regions. These findings suggest that rare-earth La and Ce doped MoSSe monolayer are potential candidate for spintronics, nanoelectronics and optoelectronics. Highlights: Doping effects of La and Ce atoms on electronic and optical properties of Janus MoSSe monolayer are investigated. CFV. Increasing the doping concentration, Janus MoSSe monolayer switched from semiconductor to metal. La and Ce doped MoSSe systems possess high absorption ability in the visible and infrared regions. La and Ce doped MoSSe monolayer are potential candidate for spintronics, nanoelectronics and optoelectronics.